Drug utilization study of antihypertensive drugs in a clinic in Malaysia - Jaiprakash, Heethal; K., Vinotini; ., Vindiya; ., Vsalni; ., Vikneshwara; ., Vigneswaran; ., Vinosha; Min, Voon C. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Hypertension is one of the common chronic diseases resulting in high mortality and morbidity. A plethora of new drugs are now available, and the quality of life for these patients has been altered for the better. Not many studies are conducted in Malaysia regarding drug utilization of antihypertensives and hence this study was planned. Methods: This was a pilot study conducted in a private clinic in Kuala Lumpur. Thirty patients with hypertension were chosen randomly and their prescriptions were analyzed. The data was collected in a proforma designed for the study. The proforma included variables such as age, gender, drugs used, and also regarding the names of the drugs used (generic or trade). The data was analyzed using descriptive statistics. Results: Thirty patients were recruited for the study. We found that 53% of the patients were females and 47% males. Trade names were more commonly used i.e. 64% of patients, than the generic names. Monotherapy (70%) was more frequently used than combination drugs. Beta blockers (45%) were used more often followed by calcium channel blockers (25%). Conclusions: The incidence of polypharmacy was low. The three most common groups of drugs used in hypertension were beta blockers followed by calcium channel blockers and then angiotensin converting enzyme inhibitors. Drug utilization studies are powerful exploratory tools to ascertain the role of drugs in society.